Florencio José Arnaudo, Principales tesis liberales. Editorial Pleamar. Buenos Aires 1994, XIII + 168 pp. ISBN 950-583-068-8 - Crespo, Ricardo F. (1995)
Fil: Crespo, Ricardo F. Universidad Austral; Argentina